2013
DOI: 10.1021/om400424a
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Arene C–H to C–P Functionalization Mediated by Nickel(II) and Palladium(II)

Abstract: A trisphosphine ligand with a triarylbenzene backbone was employed to support mono-nickel(II) and palladium(II) complexes. Two phosphine arms coordinated to the metal center, while the third phosphine was found to form a C-P bond with dearomatization of the central arene. Deprotonation effected the rearomatization of the central ring and metal reduction from M(II) to M(0). The overall conversion corresponds to a functionalization of an unactivated arene C-H bond to a C-P bond. This transformation represents a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…38 Examples of ligands containing two phosphines and a  system donor in the same ligand framework were reported. 39,40 Agapie and coworkers described a tris(phosphine) triphenyl benzene ligand that supports a palladium(0) metal center.…”
Section: Scheme 1 Synthesis Of Cpcme=cmepmentioning
confidence: 99%
See 2 more Smart Citations
“…38 Examples of ligands containing two phosphines and a  system donor in the same ligand framework were reported. 39,40 Agapie and coworkers described a tris(phosphine) triphenyl benzene ligand that supports a palladium(0) metal center.…”
Section: Scheme 1 Synthesis Of Cpcme=cmepmentioning
confidence: 99%
“…Contrasting compound 2, a smaller P-Pd-P angle is observed (128.78°) due to the increased flexibility of their ligand side arms. 39 In addition, it was reported that 3,5-bis(2phosphinophenyl)-pyridine exhibits less flexibility than the tris(phosphine) triphenyl benzene. 39 The coordination sphere of palladium(0) when supported by 3,5-bis(2-phosphinophenyl)pyridine consists of the two phosphine donors and an η 1 -N interaction to the central pyridine ring.…”
Section: Scheme 1 Synthesis Of Cpcme=cmepmentioning
confidence: 99%
See 1 more Smart Citation
“…11 One possibility is that Pd atoms are pi-bound to a CC double bond and 2.18 Å is a reasonable bond length in such configuration. [31][32][33] Scheme 1 describes the immobilization process based on our understanding.…”
Section: Resultsmentioning
confidence: 99%
“…[12] In contrast, a-CÀH bond activation of ligands in Ni complexes has not been reported so far,t houghafew examples of a-CÀHd eprotonation by base in Ni complexes have been observed. [13,14] The green color observedi nt he reactiono f1 with dmpbz suggested that an unstable intermediate rapidly converted into 3a,p ossibly influenced by the steric repulsion between tert-butyl groups on P 2 N 2 and methyl groupso nd mpbz in the square-pyramidal coordination geometry of 2a' (structure showni nS cheme 4).…”
mentioning
confidence: 99%